Peran Tunggal Otorita dalam Penyelenggaraan Pemerintahan Daerah Khusus Ibu Kota Nusantara - Harry Setya Nugraha; Nugraha, Harry Setya (As-Siyasi: Journal of Constitutional Law, 2025)
This study discusses the relevance of the Authority's single role in the administration of the Special Regional Government of the Nusantara Capital City (IKN), as regulated by Law Number 3 of 2022. The study critiques the inconsistency of this concept with the principles of regional autonomy and democracy. The main objective of this research is to identify arguments for the irrelevance of the Authority's single role in the IKN government and to offer alternative designs better aligned with these two concepts. The method employed in this research is a normative juridical one. The key findings of this study are as follows: first, six (6) main arguments explain why the Authority's single role in the administration of the Special Regional Government of IKN is irrelevant to the principles of regional autonomy and democracy. Second, two (2) alternative designs for the government structure are more in line with the concepts of regional autonomy and democratic principles and have the potential to be implemented in the future: 1) maintaining IKN as a Special Regional Government with a Governor and Regional People's Representative Council (DPRD) as the administrators; 2) maintaining IKN as a Special Regional Government with a Head of Authority and DPRD as the administrators.